Pathogenic Cx31 is un/misfolded to cause skin abnormality via a Fos/JunB-mediated mechanism. - Tang, C.; Chen, X.; Chi, J.; Yang, D.; Liu, S.; Liu, M.; Pan, Q.; Fan, J.; Wang, D.; Zhang, Z. (Human Molecular Genetics, 2015)
Mutations in connexin-31 (Cx31) are associated with multiple human diseases, including familial erythrokeratodermia variabilis (EKV). The pathogenic mechanism of EKV-associated Cx31 mutants remains largely elusive. Here, we show that EKV-pathogenic Cx31 mutants are un/misfolded and temperature sensitive. In Drosophila, expression of pathogenic Cx31, but not wild-type Cx31, causes depigmentation and degeneration of ommatidia that are rescued by expression of either dBip or dHsp70. Ectopic expression of Cx31 in mouse skin results in skin abnormalities resembling human EKV. The affected tissues show remarkable disrupted gap junction formation and significant upregulation of chaperones Bip and Hsp70 as well as AP-1 proteins c-Fos and JunB, in addition to molecular signatures of skin diseases. Consistently, c-Fos, JunB, Bip and Hsp70 are strikingly higher in keratinocytes of EKV patients than their matched control individuals. Furthermore, a druggable AP-1 inhibitory small molecule suppresses skin phenotype and pathological abnormalities of transgenic Cx31 mice. The study suggests that Cx31 mutant proteins are un/misfolded to cause EKV likely via an AP-1-mediated mechanism and identifies a small molecule with therapeutic potential of the disease.